2022
DOI: 10.3390/vaccines10081258
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards COVID-19 Booster Vaccines, Vaccine Preferences, Child Immunization, and Recent Issues in Vaccination among University Students in Jordan

Abstract: Although COVID-19 vaccines have been available in Jordan for more than a year, Jordan suffers from a low vaccination rate. The aim of this study was to explore attitudes towards recent issues in vaccination among university students in Jordan. We adopted a cross sectional study design using an online questionnaire distributed in a Jordanian university with a medical school chosen at random. The survey asked about COVID-19 vaccine preferences, factors affecting COVID-19 vaccine preferences, child vaccination, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Quite a large percentage of the local population were hesitant to take the vaccine. Alternatively, Syrian refugees show high willingness to vaccinate their children, with only 13.9% unwilling to do so, which is very low compared with other studies reporting high unwillingness of parents from Arab countries to vaccinate their children [ 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 74%
“…Quite a large percentage of the local population were hesitant to take the vaccine. Alternatively, Syrian refugees show high willingness to vaccinate their children, with only 13.9% unwilling to do so, which is very low compared with other studies reporting high unwillingness of parents from Arab countries to vaccinate their children [ 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 74%
“…It is influenced by factors such as complacency, convenience, and confidence. 1 Previous studies demonstrated the escalating worldwide occurrence of vaccine hesitancy in general as a global phenomenon. 14,15 Prominent factors behind vaccine hesitancy identified include safety issues, religious beliefs, beliefs that vaccines do not work, and overall lack of information.…”
Section: Introductionmentioning
confidence: 99%
“…These mutations were associated with increased recurrence of infection, transmissibility, and immune evasion even after natural immunity caused by infection or vaccine‐induced immunity. Booster doses were shown to provide a fast and significant improvement in protection against infection for all variants as they improved humoral and cellular immunity against different variants 1 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations